Genome‐wide identification and functional analyses of microRNA signatures associated with cancer pain - Kiran Kumar Bali; Deepitha Selvaraj; Venkata P. Satagopam; Jianning Lu; Reinhard Schneider; Rohini Kuner (EMBO Molecular Medicine, 2013)
Abstract Cancer pain remains a major challenge and there is an urgent demand for the development of specific mechanism‐based therapies. Various diseases are associated with unique signatures of expression of microRNAs (miRNAs), which reveal deep insights into disease pathology. Using a comprehensive approach combining genome‐wide miRNA screening, molecular and in silico analyses with behavioural approaches in a clinically relevant model of metastatic bone‐cancer pain in mice, we now show that tumour‐induced conditions are associated with a marked dysregulation of 57 miRNAs in sensory neurons corresponding to tumour‐affected areas. By establishing protocols for interference with disease‐induced miRNA dysregulation in peripheral sensory neurons in vivo, we functionally validate six dysregulated miRNAs as significant modulators of tumour‐associated hypersensitivity. In silico analyses revealed that their predicted targets include key pain‐related genes and we identified Clcn3, a gene encoding a chloride channel, as a key miRNA target in sensory neurons, which is functionally important in tumour‐induced nociceptive hypersensitivity in vivo. Our results provide new insights into endogenous gene regulatory mechanisms in cancer pain and open up attractive and viable therapeutic options.